(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
This article discusses the role of the Malay language in Science, Technology, Engineering and Mathematics (STEM) education. A brief review of the development of STEM in the Malay Achipelago, and the position of the Malay language as a marker of identity as well as its role in developing Malay culture within the mould or world-view of Islam, was conducted. The article also reviews the potential of the Malay language to further develop the body of STEM knowledge, and the meaning of science-the field which is core to the development of STEM. It is found that the Malay language is not only capable of being used as the medium of instruction in STEM education but also that its use will help to develop and advance Malay identity, character and values, even though in the Weste, STEM is considered to be secular in nature, and thus divorced from cultural and religious values. Keywords: Malay language, STEM education, identity, Islamic values